Pergeseran Makna Belis Ema Tetun: Antara Penghormatan dan Objektifikasi Perempuan - Felix Riondi Sugar; Anselmus N. Halek (Universitas Cenderawasih, 2026)
This study aims to examine the shifting meanings of the Tetun belis ema practice and the forms of objectification of women that emerge within it. The study employs a qualitative literature review method, drawing on various scholarly sources related to belis culture, patriarchy, gender relations, and feminism. Data analysis was conducted using content analysis techniques from a socio-cultural feminist perspective. The results of the study indicate that belis is fundamentally a symbol of respect for women, a bond of kinship, and a form of social legitimacy within the traditional Ema Tetun marriage. However, social developments and the influence of patriarchal culture have shifted the meaning of belis into a transactional practice that positions women as objects of economic exchange and symbols of social status. This shift is evident in the determination of the belis value based on a woman’s education, social and economic status, and physical attributes. This practice has the potential to foster subordination, marginalization, and the legitimization of male power over women. Therefore, a reconstruction of the meaning of belis is necessary so that it continues to be understood as a form of respect for women’s dignity, rather than as a legitimization of control over women.